(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
This paper studies the phenomenon of hedging in press briefing . It begins with the introduction that introduces different definitions of the term for different writers and linguists in order to show its nature . The paper discusses also the types of hedging : hedging through negation , through disclaimer , hedged performatives and hedging through complex structure . Though the former sub headings seem rather varied and many , but it is an attempt to reflect the main ways of hedging that are used by politicians in general and press briefers in special . The study supports the above mentioned linguistic devices of hedging with suitable examples where necessary . The politeness principle as a style of indirectness in conversation has been also referred to . The relation between gender and hedged language with the main characteristics of women’s speech in addition to the process of observing or violating Gricean maxims have been also mentioned throughout this study . The paper ends with the analysis of a press briefing sample with certain conclusions that have been arrived at.